Roma: The Literary Topoi of Rome in Roman Poetry (KULT_online, 2017)
The dissertation Die Großstadt als literarischer Raum in der römischen Dichtung by Elsa-Maria Tschäpe examines the representation of the city of Rome in Roman poetry. Taking into account the results of the latest research on the spatial theory within the context of Modern Literature and Classics, Elsa-Maria Tschäpe investigates various texts from Roman poetry with a focus on depictions of Rome and therefore offers a valuable overview of the literary discovery of the city that contributes to the current research of spatiality in Classical Literature.